ضغط ما بعد الصدمة النفسية لدى المراهقين الأيتام - دقلة, يمينة; باوه, هناء (جامعة الوادي - University of Eloued, 2023)
Abstract: Through the current study on the topic of post-traumatic stress among adolescent orphans, and to confirm this work, the descriptive exploratory approach was relied on in this study, and a sample consisting of 13 females and 18 males was chosen in an intentional manner, and the Davidson scale for post-traumatic stress was used. It consists of 17 items, each representing a symptom of trauma. By applying the scale, the following results were obtained: It showed that the arithmetic mean of the adolescent sample on this scale was (44.19), which is in the mean, and that the gender factor is not influential through our results, as we found a non-statistically significant difference, which is equal to 2.85. There are no differences between females and males, and the difference between them is (16.82), which is not statistically significant. From the results of the study, we can conclude that post-traumatic stress disorder includes loss, the threat of death, or the possibility of losing again. Therefore, post-traumatic stress disorder affects orphaned adolescents and their psychological state. الملخص: من خلال الدراسة الحالية لموضوع ضغط ما بعد الصدمة النفسية لدى الأيتام المراهقين ولتأكيد من هذا العمل وتم الاعتماد في هذه الدراسة على المنهج الوصفي الاستكشافي، وتم اختيار عينة متكونة من 13اناث و18ذكور بطريقة قصدية، وتم استخدام مقياس دافيدسون لكرب ما بعد الصدمة ترجمة: عبد العزيز ثابت والمكون من 17بند يمثل كل منها عرض من أعراض الصدمة. ومن خلال تطبيقالمقياس تم التوصل إلى النتائج التالية: أظهرت أن المتوسط الحسابي للأفراد عينة المراهقين على هذا المقياس بلغ (44,19)وهو يقع في المتوسط وان عامل الجنس غير مؤثر من خلال النتائج الموجودة لدينا، حيث وجدنا فرق غير دال إحصائيا والذي يساوي 2,85. لا يوجد فروق بين الإناث والذكور والفرق بينهم يساوي (16,82) وهو غير دال إحصائيا. ومن نتائج الدراسة يمكننا أن نستخلص أن اضطراب ما بعد الصدمة يتضمن الفقدان أو التهديد بالموت أو احتمالية حدوث الفقدان مرة أخرى لذا فان اضطراب كرب ما بعد الصدمة يؤثر على المراهقين الأيتام وعلى حالتهم النفسية.
مذكرة ماستر تخصص علم النفس عيادي
Keywords: post-traumatic stress, adolescents, orphans; ضغط ما بعد الصدمة، المراهقين، الأيتام